2016
DOI: 10.1038/nprot.2016.056
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale production of Plasmodium falciparum gametocytes for malaria drug discovery

Abstract: The tightly controlled induction of Plasmodium falciparum gametocytes in large-scale culture is a fundamental requirement for malaria drug discovery applications including, but not limited to, high-throughput screening. This protocol uses magnetic separation for isolation of hemozoin-containing parasites in order to (i) increase parasitemia, (ii) decrease hematocrit and (iii) introduce higher levels of young red blood cells in a culture simultaneously within 2-4 h. These parameters, along with red blood cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…We utilized our established protocol for gametocytogenesis induction49, with modifications consisting in the maintenance of the cultures at 15% gametocytemia and 1% haematocrit (hct) post MACs column isolation on day 8 of gametocytogenesis and daily media exchange until the parasites were used for assays on day 12.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized our established protocol for gametocytogenesis induction49, with modifications consisting in the maintenance of the cultures at 15% gametocytemia and 1% haematocrit (hct) post MACs column isolation on day 8 of gametocytogenesis and daily media exchange until the parasites were used for assays on day 12.…”
Section: Methodsmentioning
confidence: 99%
“…N-acetylglucosamine (GlcNac), at a concentration of 50 mM, was previously shown to stop the multiplication of asexual parasites over a 72 h period without harm to gametocyte development [26]. In our system, several initial tests with asynchronous and synchronous cultures allowed us to determine that GlcNac at a concentration of 20 mM for 48 h successfully inhibited asexual parasite growth in the Cellbag (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Even in parasite lines with relatively high conversion rates, gametocytes usually represent less that 1% of the parasitized cells within a given culture [6, 15] and, consequently, the amount of gametocyte material that can be isolated from in vitro systems is not conducive to large or high-throughput studies. Recently, Delves et al [25] and Duffy et al [26] reported detailed protocols for the routine culture of gametocytes in volumes between 0.2 and 200 ml.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of P. falciparum gametocyte differentiation and gametocyte culturing were performed as previously described [62]. Compound activity against early stage gametocytes (covering the development from stage I to IIb/III) and late stage gametocytes (stage IV to V) of the recombinant P. falciparum line NF54 Pfs16 was assessed in concentration-response assays, in two experimental replicates consisting of two technical repeats each, at a highest concentration of 40 μM, as described earlier [30, 51].…”
Section: Methodsmentioning
confidence: 99%
“…Stage V gametocyte cultures at day 11 post-induction (24 h incubation) or day 12 post-induction (2 h incubation), obtained as previously described [62], were dispensed into 384 well plates (Axygen®) at 0.5% hematocrit and ~5% gametocytemia and incubated at 37 °C with 90% N 2 , 5% CO 2 , 5% O 2 with compounds for the indicated exposure durations. Compounds were tested in concentration-response assays at a final highest concentration of 40 μM, in two biological replicates, without technical repeats.…”
Section: Methodsmentioning
confidence: 99%